The complete mitochondrial genome sequence of Liobagrus mediadiposalis (Teleostei, Siluriformes, Amblycipitidae). Issue 2 (12th December 2017) - Park, Chang Eon; Kim, Min-Chul; Kim, Kgu-Hwan; Park, Hee Cheon; Shin, Jae-Ho
Abstract: The south torrent catfish Liobagrus mediadiposalis (Teleostei, Siluriformes, Amblycipitidae) is an endemic species of Korea. The complete mitochondrial genome sequence consisted of 16, 534 base pairs (bp) encoding 13 protein-coding genes (PCGs), two ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and two non-coding regions. The overall base composition of L. mediadiposalis was G + C: 44.8%, A + T: 55.2%, apparently with a slight AT bias. Phylogenetic analysis showed that L. mediadiposalis was closely related to Liobagrus reinii.